Christian identity - Van der Borght, Ed. A. J. G., 1956- (Studies in Reformed theology ;, 2008)
In this age of globalization, a need for a communicative explanation of personal and group positions also motivates Christians to describe more precisely their identity in relation to other actors in society. What makes a Christian a Christian? What is specifically Christian in social acions or political calling? Is there a difference between Christian justice and justice in general - and the way Christians deal with justice? What is our calling as Christians? The contributions in this volume are the result of the 6th biannual IRTI conference in Seoul 2005 on this theme.